The Relationship of Family Support with Compliance with Blood Sugar Control in Diabetes Mellitus Patients - Ersawati, Ajeng; Rosyid, Fahrun Nur (GLOBAL HEALTH SCIENCE GROUP, 2024)
Diabetes mellitus (DM) is a condition where blood sugar levels increase because the pancreas cannot carry out its function optimally and efficiently in producing sufficient amounts of insulin. Indonesia is the 7th country most affected by diabetes with an incidence of 10.7 million people. One factor that plays an important role in maintaining blood sugar control is family support because patients with good support also have good blood sugar control. This study aims to determine whether there is a relationship between family support and compliance with blood sugar control in diabetes mellitus sufferers in the Kartasura Health Center working area. The research method is quantitative with analytical observational type using a cross sectional approach. The sample taken was 174 respondents who received treatment at the Kartasura Community Health Center. Sampling was taken using accidental sampling. Data collection was carried out on respondents using a questionnaire. Univariate data analysis used the Kolmogorov Smirnov test and bivariate using the correlation test (Spearman Rank). The research results show that there is a relationship between family support and compliance with blood sugar control in diabetes mellitus sufferers with p-value=0.005 or <0.05. The conclusion of this research is that the better the family support, the better the patient's compliance in controlling blood sugar.